A PROFILE OF LOCAL SUBSIDIARY MANAGERS - Daniels, John D. (Academy of Management Journal, 1973)
The article discusses biographic data of several local subsidiary managers. Biographic data was gathered from 130 non-American executives in 27 subsidiaries of 12 U.S. companies in Belgium, France, and Great Britain. The biographic data resulted in some discrepancies with conclusions that are usually gathered from material related to this topic. Among the better educated managers, the expatriates advance faster than the non-American. According to the author, the three most plausible reasons are that the people sent abroad are individuals who have showed rapid upward mobility by virtue of past performance or qualifications, Americans are able to advance faster, or innovations within the firms originate in the U.S. so that U.S. personnel have the experience to transfer the innovations.